Evaluation of maternal and fetal outcomes in pregnancy with heart disease - Mulik, Jayshree; Patil, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Heart diseases complicate >1% of all pregnancies and is the leading indirect cause of maternal deaths. Present study attempted determining the maternal and fetal outcome in pregnant women with heart disease using various relevant parameters. Methods: A total of 44 consecutive cases of heart disease with pregnancy that were admitted at the study centre from December 2013 to August 2015 were included and analyzed for outcome with respect to age, parity, associated comorbidities, nature of cardiac lesions, type of valvular involvement, NYHA functional class, type of anaesthesia used, mode of delivery, maternal outcome, fetal outcome, birth weight of babies and maternal and fetal mortality, if any. Results: Rheumatic heart disease 26 (59.1%) was the commonest lesion observed to be affecting pregnant patients, followed by congenital heart disease (10, 22.7%). Mitral valve (30, 68.2%) was found most commonly affected, followed by aortic valve (10, 22.7%). Regurgitant lesions (26, 59.09%) were commoner than stenotic ones (14, 31.81%). Four (9.1%) patients went into left ventricular failure and had to be admitted to ICU. Of these, one patient (2.3%) died. Conclusions: Maternal heart disease is one of the important causes of maternal mortality. The obstetrician needs to have strong suspicion of the entity right from the start, so as to improve upon the maternal as well as fetal outcomes.